Does size matter? The influence of large clients on office-level auditor reporting decisions - Reynolds, J.Kenneth; Francis, Jere R (Journal of Accounting and Economics, 2000)
Large clients create an economic dependence that may cause auditors to compromise their independence and report favorably to retain valuable clients. Economic dependence is measured as a client's size relative to the size of the office that contracts for the audit and issues the audit report. We find no evidence economic dependence causes Big Five auditors to report more favorably for larger clients in their offices. However, larger clients also pose greater litigation risk, and we do find that Big 5 auditors report more conservatively for larger clients, suggesting that reputation protection dominates auditor behavior.